AB0027 B-Cell Activating Factor (BAFF) Binding Receptors (BBR) on B Cells: Characterization in Patients with Rheumatoid Arthritis (RA) Receiving Biological Therapies: Anti-TNF, Anti-Il6r and Anti-Ctla4: A Longitudinal Study. (10th June 2014) - Hernández Flόrez, D.; Valor, L.; de la Torre, I.; Gallego, A.; Chamizo, E.; del Río, T.; Martinez, L.; Gonzalez, C.; Lopez-Longo, J.; Monteagudo, I.; Naredo, E.; Montoro, M.; et al.
Abstract : Background: The treatment of rheumatoid arthritis (RA) has improved in the last years because of both: an increased understanding of its pathogenesis and the use of biological therapies. It is well known that B cells play a pivotal role in the development of autoimmune processes mainly as a precursor of antibody-secreting cells and also as antigen-presenting cells (APC). The development, survival and maturation of B-cells depend among others factors on specific membrane receptors. In this longitudinal study we have evaluated BAFF-Binding Receptors [BBR: BAFF-R (B-cell activating factor), TACI (transmembrane activator and calcium-modulating and cyclophilin ligand interactor), BCMA (B-cell maturation antigen)] and the activation marker CD86 expression on B-cells in response to three different therapeutic targets, anti-TNF (tumor necrosis factor): [infliximab (IFX), adalimumab (ADA), etanercept (ETA)]; anti-IL6R (Interleukin-6 receptor): tocilizumab (TCZ) and the anti-CTLA4 (Cytotoxic T-Lymphocyte Antigen 4): abatacept (ABC). Objectives: To investigate the possible role of biological therapies in B-cells phenotype changes and therefore in their survival/maturation process in patients with RA. Methods: 39 patients diagnosed with RA and naive to biological therapies, started treatment with ADA (n=7), ETN (n=9) IFX (n=3), TCZ (n=15) and ABC (n=5). They were assesed at baseline and every 4 month for one year. Peripheral whole blood was stained with conjugated monoclonal antibodies directed to CD19, CD27, IgD, CD38, BAFF-R, BCMA, TACI and CD86 and then evaluated by multiparametric flow cytometry. The patients were classified according to the therapeutic target: ADA+ETN+IFX (anti-TNF), TCZ (anti-IL6R) and ABC (anti-CTL4). Results: We found decreased percentages (%) of memory B-cells (CD19+/CD27+) and an inversely proportional increase of naïve B-cells (CD19+/CD27−) in the groups ABC vs. anti-TNF and TCZ. Regarding the B-cell subsets, % of memory resting B-cells (CD19+/IgD+/CD38−) were lower in all three groups being more marked in the ABC group, whereas % of post-germinal center B-cells (CD19+/IgD−/CD38+) were lower in anti-TNF and ABC vs. TCZ. Regarding the BBR expression on memory B-cells, we found a decreased TACI expression in TCZ vs. anti-TNF and ABC, and also a decreased CD86+ expression in ABC vs. anti-TNF and TCZ. Conclusions: In this exploratory study, the regulatory effect (TACI) on the B-cell phenotype and CD86 expression was more evident in the TCZ and ABC groups. These changes might be explained by two different key pathways for immune-regulation, the effect of cytokines and the cell-cell interaction process. Our data suggested that the monitoring of B-cells may be useful to further understand the role of specific B-cell receptors in the pathogenesis of RA and its association with clinical response to biological therapies. Disclosure of Interest: D. Hernández Flόrez: None declared, L. Valor: None declared, I. de la Torre: None declared, A. Gallego: None declared, E. Chamizo: None declared, T. del Río: None declared, L. Martinez: None declared, C. Gonzalez: None declared, J. Lopez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, E. Naredo Grant/research support: UCB and MSD, Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, M. Montoro: None declared, M. Salvat: None declared, L. Carreño Perez: None declared DOI: 10.1136/annrheumdis-2014-eular.3191